Upaya Pengelolaan Percetakan Biru dengan Analisis SWOT - Anang Setyawan (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam (e-Journal), 2022)
Printing is an industry that is experiencing rapid development. The purpose of this study was to determine the efforts to manage the blueprint with POAC management and SWOT analysis. This type of research is a qualitative descriptive field research with data collection techniques, interviews, observation and documentation. The data analysis technique used is the IFAS, EFAS, IE, SPACE and SWOT matrix. The results showed that the Planning, Organizing, Actuating and Controlling processes were carried out with the main target being students so that the POAC activities were adjusted to the course schedule, the results of the IFAS 3.88 and EFAS 3.88 analysis, with the highest assessment on the SO strategy, namely maximizing the power to seize existing opportunities, namely more innovating with products, expanding market share, and making affordable or discounted prices. Percetakan Biru is in quadrant 1 which means that it is growing and developing.